Induced Mutagenesis and Comparative Genomics of Raoultella sp. 64 for Enhanced Antimony Resistance and Biosorption - Tianhua Huang; Shiran Cao; Xiaohan Li; Chuhan Wang; Xiawei Peng (Microorganisms)
Antimony-resistant bacteria are potential natural resources for the bioremediation of mining soil pollution. A Raoultella sp. 64 strain was isolated from antimony-contaminated soil. To enhance its Sb resistance abilities, this strain was transported into space aboard the Shenzhou spacecraft for space breeding, resulting in a mutant strain, Raoultella sp. D9. The whole genomes of Raoultella sp. 64 and mutant strain Raoultella sp. D9 were sequenced, revealing the genomic information for the bacterium. Comparative genomic analysis was then carried out to identify differential functional genes. The adsorption conditions for Sb(III) were optimized and refined. Further, Fourier transform infrared spectroscopy (FTIR) was used to determine the adsorption of antimony. Results show that strain D9 exhibits a higher tolerance to Sb(III), and Sb resistance genes were identified in both Raoultella sp. 64 and D9. Analysis of the differential functional genes indicated that the increased copy number of plsX may lead to a higher lipid content in the cell membrane, thereby enhancing the cell’s resistance to heavy metals. Mutant strain D9 exhibited better biosorption capacity compared to strain 64. FTIR studies showed that key functional groups, including -OH, C-N, C-H, and C-O, are likely to have participated in Sb(III) biosorption. Further study of the differential functional genes could provide a basis for future research and the subsequent development of technologies for the remediation of Sb-contaminated sites.